Implementation of Genetic Algorithm Theory in Determining the Composition of Food Ingredients - Haris Maulana; Sefty Rizqi Annisa; Vera Rosnia (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2021)
The problem of determining the structure of the elements of food that is good for daily use is a problem that looks small but is actually important for the health of the body. A hereditary calculation that has an unwavering quality in creating an ideal result can be used for this problem. In this review, 138 information about food ingredients and their substances were used for testing. Information will be handled with hereditary calculation techniques that combine the processes of recognition, assessment, recombination, hybrid and change. From this information a population will be formed which has a population size of 20 and each chromosome has 10 qualities where the value of each quality is the file quantity of food ingredients in the data set. The hybrid probability values ​​and the changes used were 0.7 and 0.05. The best mixes of foodstuffs are those which, when added together for each healthful substance, will yield values ​​that most closely approximate the amounts required for each type of nutrient required in a day. The value of the amount of aggregate required.